Propionibacterium acnes Causing Mediastinal Infection following Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration - Katherine Janssen; Joseph Keenan; Roy Cho; Erhan Dincer (Case Reports in Medicine)
Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is now a standard of care to sample mediastinal lymph nodes and masses with high diagnostic accuracy and low complication rates. However, the procedure has potential complications that might be life-threatening. Here, we present the first case of Propionobacterium acnes (P. acnes) causing mediastinitis following EBUS-TBNA of a subcarinal lymph node.